Month and Season of Birth as a Risk Factor for Alzheimer's Disease: A Nationwide Nested Case-control Study - Anna-Maija Tolppanen; Riitta Ahonen; Marjaana Koponen; Piia Lavikainen; Maija Purhonen; Heidi Taipale; Antti Tanskanen; Jari Tiihonen; Miia Tiihonen; Sirpa Hartikainen (Korean Society for Preventive Medicine, 2016)
Objectives: Season of birth, an exogenous indicator of early life environment, has been related to higher risk of adverse psychiatric outcomes but the findings for Alzheimer's disease (AD) have been inconsistent. We investigated whether the month or season of birth are associated with AD. Methods: A nationwide nested case-control study including all community-dwellers with clinically verified AD diagnosed in 2005 to 2012 (n=70 719) and up to four age- sex- and region of residence-matched controls (n=282 862) residing in Finland. Associations between month and season of birth and AD were studied with conditional logistic regression. Results: Month of birth was not associated with AD (p=0.09). No strong associations were observed with season (p=0.13), although in comparison to winter births (December-February) summer births (June-August) were associated with higher odds of AD (odds ratio, 1.03; 95% confidence interval, 1.00 to 1.05). However, the absolute difference in prevalence in winter births was only 0.5% (prevalence of those born in winter were 31.7% and 32.2% for cases and controls, respectively). Conclusions: Although our findings do not support the hypothesis that season of birth is related to AD/dementia risk, they do not invalidate the developmental origins of health and disease hypothesis in late-life cognition. It is possible that season does not adequately capture the early life circumstances, or that other (postnatal) risk factors such as lifestyle or socioeconomic factors overrule the impact of prenatal and perinatal factors.